EFEKTIVITAS DAN KONTRIBUSI PAJAK HOTEL, PAJAK RESTORAN, DAN PAJAK HIBURAN TERHADAPPENDAPATAN ASLI DAERAH KOTA BATAM - Suyanti, Suyanti; Natalia, Erni Yanti (LPPM Universitas Putera Batam, 2024)
This research aims to determine the effectiveness and contribution of hotel tax, restaurant tax andentertainment tax to Batam City's original regional income. This research is qualitative research with adescriptive analysis approach. The population in this study is the projection and realization of thefinancial reports of the Batam City Regional Revenue Agency for 2019-2021 using a random samplingmethod based on regional location (Cluster Random Sampling) by collecting data from the officialwebsite of the Regional Revenue Information System or SIEPENDA of Batam City. From the resultsResearch shows that the level of effectiveness of hotel, restaurant and entertainment tax collection onBatam City's PAD can be said to be effective. This is supported by Batam being a region that relies onthe tourism sector as a source of PAD. The contribution of Hotel, Restaurant and Entertainment Taxesto Batam City's PAD is less effective. Based on the results of the ratio calculations that have beencarried out, Batam City's hotel, restaurant and entertainment tax revenues contribute less to BatamCity's PAD. This is indicated by the contribution percentage being below 10%